Updated habitat suitability estimates and conservation implications for the short-tailed chinchilla Chinchilla chinchilla (Lichtenstein, 1830) (Rodentia: Chinchillidae) - Stuhler, John; Arenas-Viveros, Daniela; Salazar-Bravo, Jorge (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
The short-tailed chinchilla (Chinchilla chinchilla) is a species classified as endangered throughout its distribution and for which neither a conservation nor management plan exists. Ecological niche models (ENMs) allow detection of potential areas of occurrence for species that are rare and/or of conservation interest. Here, we built and evaluated a suite of ENMs that incorporated new records for the species in Bolivia and removed those whose veracity could not be confirmed to provide an updated estimate of the extent of suitable habitat for C. chinchilla. Following model selection based on partial ROC, omission rate, and AICc, we then projected our top models across the historical distribution of C. chinchilla to identify locations of potentially suitable habitat. An ensemble of top models highlighted suitable habitat in Argentina, Bolivia, Chile, and Peru, with values of probability of suitable habitat up to 0.72. Together, these results demonstrate that suitable habitat still exists across the historical range of this species, provide insight into the climatic niche of this species, and highlight areas across the four countries for which future surveys of wild populations may be worthwhile.
Keywords: Andes; Ecological niche model; Maxent; Short-tailed chinchilla; South America